2021
DOI: 10.2166/wst.2021.234
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of active coagulant agent extraction method from Moringa Oleifera seeds for municipal wastewater treatment

Abstract: An enhanced and different method for the active coagulant agent extraction from Moringa Oleifera seeds powder (MOSP) was established and compared to the conventional extraction method in distillate water. In the improved method, MOSP were extracted using sodium chloride as solvent at different concentrations to extract more coagulant agent from Moringa Oleifera and enhance coagulation activity. In this study, MOSP were initially processed and oil content was removed to minimize coagulant concentration usage (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…Thus, the highest f locculation ef f iciency obtained with sodium chloride extract among the three solvents tested. This result is in agreement with the work of Bouchareb et al (2021) who used 1M sodium chloride solution to extract active coagulating agent f rom M. oleifera seeds f or use in municipal wastewater treatment and reported 97% turbidity removal with 140 g/L of 1 M NaCl extract against 88% obtained with 170 mg/L of aqueous extract. Okuda et al (1999) also reported that 1M sodium chloride solution was more ef f icient than distilled water in extracting active coagulant f rom M. oleifera seeds f or use in synthetic wastewater treatment.…”
Section: Effects Of Extracting Solvent On Flocculation Efficiency Of ...supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the highest f locculation ef f iciency obtained with sodium chloride extract among the three solvents tested. This result is in agreement with the work of Bouchareb et al (2021) who used 1M sodium chloride solution to extract active coagulating agent f rom M. oleifera seeds f or use in municipal wastewater treatment and reported 97% turbidity removal with 140 g/L of 1 M NaCl extract against 88% obtained with 170 mg/L of aqueous extract. Okuda et al (1999) also reported that 1M sodium chloride solution was more ef f icient than distilled water in extracting active coagulant f rom M. oleifera seeds f or use in synthetic wastewater treatment.…”
Section: Effects Of Extracting Solvent On Flocculation Efficiency Of ...supporting
confidence: 92%
“…Moringa oleifera seed oil has several applications including usage as biodiesel f eedstock. It is theref ore good to extract the oil bef ore coagulant extraction to reduce the bulk of the coagulant Bouchareb et al (2021). Furthermore, the oil content may interf ere with the activity of the coagulating agent in M.oleifera This result also agrees with that of Skaf et al…”
Section: Comparison Of the Flocculation Efficiency Of Extract Of Defa...supporting
confidence: 86%
“…The peaks between 15 and 40 degrees could be representative of various substances such as lipids, proteins, carbohydrates, and ash [48,49].…”
Section: Xrd Analysismentioning
confidence: 99%
“…This result can be related to the organic nature of the bio-coagulant[12]. As mentioned in the literature, the activity of natural coagulants is due to the long chains of proteins contained in their molecules, which are responsible for pollutant aggregation and floc formation[48]. On the contrary, metal-based coagulants hydrolyze in water and release H + ions, resulting in a pH decrease.…”
mentioning
confidence: 96%
“…The turbidity removal efficiency is significantly influenced by the active components from natural coagulants. Therefore, these active substances are responsible for coagulation, for instance: proteins [23,28]; polyphenols [29], polysaccharide [30], starches [31,32] and cellulose [33].…”
Section: Introductionmentioning
confidence: 99%